Gilpinia infuscalae Wang & Wei, sp. nov. and a key to the Chinese Gilpinia species (Hymenoptera: Diprionidae) - Wang, Hannan; Smith, David R.; Xiao, Wei; Niu, Gengyun; Wei, Meicai (Zootaxa, 2019)
Gilpinia infuscalae Wang & Wei, sp. nov. (Hymenoptera: Diprionidae) from China is described. It is similar in color to G. nigra Okutani, 1958 from Japan but differs in the strongly infuscate wings, the simple inner spur of hind tibia and the unique lancet. The host plant is Pinus massoniana Lamb. (Pinaceae). A key to known species of Gilpinia from China is provided.